اسلامی بینکاری میں شرکت و مضاربت کی مروجہ اشکال کا جائزہ - سلمان احمد خان; غلام نبی علوی (jihat-ul-islam, 2019)
There are different aspects of distribution of profit in Islamic banks. A keen review is required to evaluate the accuracy of this profit distribution. This article examines some of these aspects. Islamic banks keep a portion of profit as a reserve but this profit is not given to the client who is leaving the bank, instead it is awarded to a new client who is replacing the old one. This study suggests to confer this profit to the old client as it is earned by his money not by the wealth of a new depositor. All conditions of partnership also show the same view. This study will also provide detailed Shariah aspects of 'Dminishing Musharakah' practiced in Islamic banks, which is mostly the combination of 'Ijarah' and ' Bai'. It is also necessary for bank to provide details of profit and loss to the depositors; to inform them about the transactions in which negligence of the bank is involved and not to make the depositors habitual to get the profit forever. This study also condemns the viewpoint to provide guarantee to the depositor for their principal amount. Constantly making 'Hiba' from bank to the depositors is also against the goals of Shariah. The study will furnish the solutions for the problems faced by Islamic banks in above mentioned aspects. We rightly claim that Islaam is a complete code of life, so, its guidelines are also very comprehensive for every field of life, there is only need to prove it in an ideal manner.